2007
DOI: 10.1007/s11881-007-0002-1
|View full text |Cite
|
Sign up to set email alerts
|

Speech development patterns and phonological awareness in preschool children

Abstract: To examine the association between speech production and early literacy skills, this study of 102 preschool children looked at phonological awareness in relation to whether children were delayed, typical, or advanced in their articulation of consonants. Using a developmental typology inspired by some of the literature on speech development (Kahn and Lewis, The Kahn-Lewis phonological analysis, 1986; Shriberg, Journal of Speech and Hearing Research 36(1):105-140, 1993a), we found that failure to master the earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 93 publications
(114 reference statements)
3
36
0
6
Order By: Relevance
“…The performance of phonological delayed children in PA skills corresponds to their delay in speech production. Since both speech production and PA need representation of phonological structure (12), we believe delay in early phonological development also postpone other skills that need phonological representation; this is consistent with Mann and Foy (2007) (12).…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…The performance of phonological delayed children in PA skills corresponds to their delay in speech production. Since both speech production and PA need representation of phonological structure (12), we believe delay in early phonological development also postpone other skills that need phonological representation; this is consistent with Mann and Foy (2007) (12).…”
Section: Discussionsupporting
confidence: 70%
“…Some researchers have indicated the effect of error type on PA. They found that children with more atypical errors experience inferior performance in PA skills (12,15,16). The literature has also shown that there is a positive relation between speech sound accuracy measured by percent consonant correct (PCC) and PA skills (17).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As diferenças individuais em vocabulário, repetição de não-palavras e consciência fonológica são fatores importantes para o prognóstico do desenvolvimento da leitura e das habilidades relacionadas. O que as pesquisas mostram é que o caminho mais efetivo para a aprendizagem da leitura passa pelo desenvolvimento da consciência fonêmica 26 .…”
Section: Introductionunclassified